2016
DOI: 10.1007/s00345-016-1917-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in RNA-induced silencing complex genes and prostate cancer

Abstract: According to our data, rs3742330, rs4961280 and rs7813 qualify for potentially protective genetic variants against PCa progression. These variants were not shown to be associated with PCa risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In general, 70 relevant articles were originally chosen from different electronic databases. According to the inclusion and exclusion criteria, 55 articles were eliminated and 15 qualified articles (9 articles referring to rs2740348, 15 , 18 , 22 , 28 11 articles referring to rs7813, 15 17 , 19 , 22 25 , 29 31 and 5 articles referring to rs3744741 15 , 16 , 22 24 ) were finally included in the meta-analysis ( Figure 1 ). Specifically, details of the eliminated articles are shown in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, 70 relevant articles were originally chosen from different electronic databases. According to the inclusion and exclusion criteria, 55 articles were eliminated and 15 qualified articles (9 articles referring to rs2740348, 15 , 18 , 22 , 28 11 articles referring to rs7813, 15 17 , 19 , 22 25 , 29 31 and 5 articles referring to rs3744741 15 , 16 , 22 24 ) were finally included in the meta-analysis ( Figure 1 ). Specifically, details of the eliminated articles are shown in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variants in the GEMIN4 gene might lead to a decreased inhibitory effect on the proliferation of hepatocarcinoma cells and simultaneously have an impact on the DNA repair system by altering the expression of proliferation-associated genes and DNA repair genes. 32 Several studies have found that genetic variants in the GEMIN4 gene not only alter the susceptibility to cancer, 15 19 but also influence the survival time of patients with cancer. 33 , 34 However, as far as we know, most of these studies are small-scale case–control studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it was shown that some SNPs in miRNA biogenesis genes are associated with the risk of various cancers. Examples include (i) the rs3742330 (A>C) SNP located in the 3' UTR of DICER1 that affects DICER1 mRNA stability and is associated with susceptibility and malignancy in gastric cancer [74,75], increased survival of Tcell lymphoma patients [76] and lower prostate cancer aggressiveness [77]; (ii) the rs78393591 SNP in DROSHA and rs114101502 SNP in ZCCHC11 (TUTase responsible for pre-miRNA uridylation and subsequent DICER1 cleavage inhibition) associated with the risk of breast cancer [78]; and (iii) the rs11786030 and rs2292779 SNPs in AGO2, rs9606250 SNP in DGCR8, and rs1057035 SNP in DICER1 associated with the survival of breast cancer patients [79]. Additionally, the SNPs rs2740348 C>G and rs7813 C>T in GEMIN4, a gene involved in miRISC formation and miRNA-duplex unwinding, were implicated in the risk of several cancers, although the results were not conclusive [80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%